The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2001
DOI: 10.1359/jbmr.2001.16.2.361
|View full text |Cite
|
Sign up to set email alerts
|

Indapamide, a Thiazide-Like Diuretic, Decreases Bone Resorption In Vitro

Abstract: We recently showed that indapamide (IDP), a thiazide-related diuretic, increases bone mass and decreases bone resorption in spontaneously hypertensive rats supplemented with sodium. In the present study, we evaluated the in vitro effects of this diuretic on bone cells, as well as those of hydrochlorothiazide (HCTZ), the reference thiazide, and acetazolamide (AZ), a carbonic anhydrase (CA) inhibitor. We showed that 10

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0
2

Year Published

2006
2006
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(26 citation statements)
references
References 50 publications
0
24
0
2
Order By: Relevance
“…The exact role of thiazides on bone cell is still under debate [51]. Some studies indicate that thiazides are capable of reducing osteoclastic activity [52,53]. Moreover, it has been suggested that thiazides directly stimulate osteoblast differentiation and bone mineral formation, independent of their effects in the kidney [54,55].…”
Section: Discussionmentioning
confidence: 99%
“…The exact role of thiazides on bone cell is still under debate [51]. Some studies indicate that thiazides are capable of reducing osteoclastic activity [52,53]. Moreover, it has been suggested that thiazides directly stimulate osteoblast differentiation and bone mineral formation, independent of their effects in the kidney [54,55].…”
Section: Discussionmentioning
confidence: 99%
“…In vitro , thiazides have a selective effect on human osteoblast-like cell lines, directly stimulating osteocalcin production in human osteoblasts and increasing the expression of thiazide-sensitive sodium chloride cotransporter in osteoblast-like cells, which is the target of thiazide diuretics 141143. The mitogenic action of thiazide and the thiazide-related diuretic, indapamide, has been shown to be in part due to increased osteoblastic cell proliferation 144,145. This in vitro effect was also associated with inhibition of osteoclastic bone resorption as a result of the reduction of osteoclastic cell differentiation mediated through direct inhibition of hematopoietic precursors 144,146,147.…”
Section: Potential Therapeutic Regimensmentioning
confidence: 99%
“…Bisphosphonates also reduce urinary calcium excretion in normal and hypercalciuric patients (187, 188 ). Thiazides act by stimulating calcium reabsorption in the distal convoluted tubule and also stimulate osteoblast differentiation with a reduction in stone recurrence rate, osteoporotic fractures and an increase in BMD (187, 189196) .…”
Section: Introductionmentioning
confidence: 99%